Volition and eye movements. - Nachev, P; Husain, M; Kennard, C (2008)
Although the conceptual distinction between voluntary and automatic acts seems intuitively obvious, its neural basis remains opaque. Assigning volition--or some paraphrase such as action selection--to discrete parts of the brain arguably tells us nothing about what volition actually is in neural terms. Equally, exploring the relative sensitivity of discrete brain areas to manipulations of action choice, including its asymptote--free choice--would only be informative if voluntary processes could thereby be reliably isolated. Unfortunately, such manipulations are subject to ineliminable confounds, such as the complexity of the underlying condition-action associations. Here we propose an adaptation of a classic oculomotor task--saccadic choice with asynchronous targets--where the processes engaged in free choice manifest as interference in the performance of an automatic task, thereby circumventing the difficulties in parameterising volition. We suggest that this task may be useful in probing deficits in voluntary action in pathological states.